2019
DOI: 10.2319/052318-392.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different settings for 940 nm diode laser on expanded suture in rats

Abstract: Objectives: To evaluate the effects of the Indium Gallium Arsenide Phosphoride (InGaAsP) diode laser at different energy levels on orthopedically expanded midpalatal sutures of rats. Materials and Methods: Eighty Wistar rats were randomly divided into four groups: a control group and low-, moderate-, and high-level laser groups with amounts of energy irradiated at 0 J, 18 J, 42 J, and 60 J, respectively. Each group was divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…As previously reported, an expansion spring fixed to the upper incisors was used to expand the premaxilla in rats. 5,6 Mid-palatal separation in rats was reported to be achieved with only 50 to 70 g force. 5 Thus, in this study, all sutures were expanded with 70 g force.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, an expansion spring fixed to the upper incisors was used to expand the premaxilla in rats. 5,6 Mid-palatal separation in rats was reported to be achieved with only 50 to 70 g force. 5 Thus, in this study, all sutures were expanded with 70 g force.…”
Section: Discussionmentioning
confidence: 99%
“…4 More rapid formation of new bone in the expanded mid-palatal suture may be useful to shorten the retention period and there is also evidence that this may inhibit relapse of the skeletal transverse expansion. Purposefully, practitioners have worked on the acceleration of new bone formation using different methods such as laser stimulation 5 and the use of agents including transforming growth factor, 6 bisphosphonates, 7 antioxidants, 8 and lactoferrin. 9 More recently, researchers have studied antioxidants more closely due to their stimulatory effect on bone metabolism via osteoblastic stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is reported that lower levels of stimuli increase physiological functions, while high-intensity stimulation can decrease and even inhibit them. 16 The results obtained by Tas Deynek and Ramoglu 10 confirms the theory of the therapeutic window, where the authors observed that the best reparative effects on rats were obtained at a lower dose (18 J/cm 2 ), with a higher initial concentration of osteocytes, subsequent increase of osteoblasts, blood vessels, and new bone tissue. By contrast, groups who received higher doses of radiation showed increased inflammation and decreased regeneration.…”
Section: Discussionmentioning
confidence: 63%
“…Although it has been shown that the use of a lower-power laser improves bone regeneration results, there is still no consensus regarding the dose needed to obtain the desired results. According to the law of Arndt-Schultz, 10 , 16 there is a therapeutic window of the effective dose range, due to the different stimulus intensities, they can increase or decrease physiological functions. In addition, it is reported that lower levels of stimuli increase physiological functions, while high-intensity stimulation can decrease and even inhibit them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation